"FREE TRADE" IN HIGHER EDUCATION The Meta University - Graves, William H. (Online Learning, 1997)
The Internet can be a tool for increasing access to education while also maintaining or improving the quality of students’ learning. But if information technology is "bolted onto" existing programs, instructional costs increase. Instead, higher education must learn to use technology to disaggregate and disintermediate some of its current instructional programs and to recombine the resulting components into more flexible services that can compete in an educational "free market."